Pointing the way to intelligent automation - Hollingum, Jack (Industrial robot, 1997)
Outlines talks given at a masterclass organized by the Institution of Electrical Engineers on the theme "Intelligent automation and robotics" at Bristol University in October 1996. Briefly states the content of several speeches on subjects including: brain and perception skills; machine learning and real-time control from smart machines to intelligent systems; and skilled automation and applications.